The role of political trust, perceived government efforts, peer influence, and eco-anxiety in climate change adaptation among Johor youth in Malaysia - Muhamad Halmee, Nurul Syahirah; Ma’rof, Aini Azeqa; Nashorddin, Nur Afiqah; Mohd Yusof, Nor Khairina Amira (Human Resource Management Academic Research Society, 2024)
Climate change adaptation is critical for mitigating the adverse impacts of environmental degradation, particularly among vulnerable youth populations. This study examines the role of political trust, peer influence, eco-anxiety, and climate education in predicting climate change adaptation behaviors among Johor youth, Malaysia. A quantitative approach was employed, surveying 400 participants aged 18–30 years. Data were analyzed using multiple regression to identify significant predictors of climate adaptation behaviors. The findings reveal that political trust and peer influence are the strongest predictors, followed by eco- anxiety, which showed a moderate but significant effect. Climate education was found to indirectly support adaptation behaviors by enhancing awareness and motivation. These results underscore the importance of fostering political trust and leveraging peer networks to drive climate action among youth. Practical implications for policymakers and educators include the development of programs that integrate social and psychological factors to promote proactive climate adaptation behaviors.